2000
DOI: 10.1016/s0921-5093(99)00632-2
|View full text |Cite
|
Sign up to set email alerts
|

The microstructure and linear superelasticity of cold-drawn TiNi alloy

Abstract: The microstructure and linear superelasticity of cold-drawn TiNi alloy have been investigated using CTEM, HREM and in-situ transition electron microscopy observations and tensile tests. The microstructural evolution procedure of the martensite variants with increasing degree of area reduction was found to be that the quantities of (111( ) Type I, (001) compound, (011) Type I and (111) Type I twinning plates increase gradually with decreasing the amount of the 011 Type II twinning bands. The corresponding domin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
22
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(24 citation statements)
references
References 16 publications
1
22
0
1
Order By: Relevance
“…We refer to the associated shape recovery as twinning-induced elasticity (TIE). In the literature, TIE was referred to as ''linear superelasticity'' [24][25][26] or ''twinning pseudoelasticity'' [23]. Figure 1b shows examples of stress/strain curves from a NiTi SMA in the TIE state.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We refer to the associated shape recovery as twinning-induced elasticity (TIE). In the literature, TIE was referred to as ''linear superelasticity'' [24][25][26] or ''twinning pseudoelasticity'' [23]. Figure 1b shows examples of stress/strain curves from a NiTi SMA in the TIE state.…”
Section: Introductionmentioning
confidence: 99%
“…1a is not observed. However, TIE is known to provide lower reversible strains as compared to PE SMAs [23,24,27,28]. Typically, strains of the order of 3 % can be fully recovered.…”
Section: Introductionmentioning
confidence: 99%
“…It has been confirmed that the properties of TiNi SMAs can be affected by various thermal mechanical treatments such as aging in Ni-rich TiNi alloys, [1][2][3] cold rolling 4) and thermal cycling, 5) moreover, the addition of a third element to replace Ni and/or Ti has a substantial effect on phase transformation behavior of TiNi binary alloys. It is well known that the Ms temperature decreases with the addition of V, Fe, Co, but increases remarkably with element such as Au, Pd, Pt, and Hf.…”
Section: Introductionmentioning
confidence: 99%
“…It was shown [2][3][4] that this alloy system possesses a high pseudoelastic, also called superelastic effect. However, all previously studied stress strain loops showing pseudoelastic behaviour in these alloys, as well as in most SMA systems such as Ti-Pd-Ni [5], Ni-Ti [6,7], Fe-Pt [8], Cu-Al-X where X is Mn, Zn, Ni [9,10] etc. are due to the stress induced martensite transformation (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…: highly nonlinear hysteretic behaviour, strongly dependent on the stress or deformation rates [12,13], not stable with stress cycling, and with strong temperature dependence of the superelastic loop and critical stress values [4,10,11]. While the Ti-Ni [6] seems attractive having 100% recovery and a quasilinear behaviour, though it possesses small elastic strain values (4%) at very high stress values above 1GPa. On the other hand, in the 20% compressive strain in the martensite phase of single crystalline Ni-Mn-Ga alloy was obtained [14].…”
Section: Introductionmentioning
confidence: 99%